2004
DOI: 10.1038/sj.ejcn.1601990
|View full text |Cite
|
Sign up to set email alerts
|

Does vitamin C supplementation influence the levels of circulating oxidized LDL, sICAM-1, sVCAM-1 and vWF-antigen in healthy male smokers?

Abstract: Objective: To examine the effects of vitamin C supplementation on the concentration of oxidation markers, in particular, circulating oxidized LDL (OxLDL) and on endothelial activation markers. Design: Randomized double-blind, placebo-controlled crossover trial. Setting: Belgian population of the city of Leuven. Subjects: A total of 34 healthy male smokers aged 26-73 y. Intervention: Smokers were randomly assigned to receive either vitamin C (250 mg twice daily) or placebo capsules, each to be taken for 4 weeks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
11
0

Year Published

2005
2005
2013
2013

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(11 citation statements)
references
References 40 publications
0
11
0
Order By: Relevance
“…In another small study (8 participants), however, application 1 g of vitamin C per day did not improve smoking-caused alterations of FMD [110]. Similarly, in a study of 34 healthy male smokers, intake of 250 mg of vitamin C twice a day did not reduce serum soluble adhesion molecules or markers of oxidation (malondialdehyde, oxLDL) [111]. However, in a combination study comprising 44 smokers who received 60 mg of vitamin C or 60 mg of vitamin C plus 480 mg Enzogenol (a flavonoid extract from Pinus radiata) per day for 12 weeks, vitamin C alone improved FMD.…”
Section: Anti-oxidative Treatment Trials To Reduce Smoking-caused Cvdmentioning
confidence: 97%
“…In another small study (8 participants), however, application 1 g of vitamin C per day did not improve smoking-caused alterations of FMD [110]. Similarly, in a study of 34 healthy male smokers, intake of 250 mg of vitamin C twice a day did not reduce serum soluble adhesion molecules or markers of oxidation (malondialdehyde, oxLDL) [111]. However, in a combination study comprising 44 smokers who received 60 mg of vitamin C or 60 mg of vitamin C plus 480 mg Enzogenol (a flavonoid extract from Pinus radiata) per day for 12 weeks, vitamin C alone improved FMD.…”
Section: Anti-oxidative Treatment Trials To Reduce Smoking-caused Cvdmentioning
confidence: 97%
“…While some studies found that ascorbic acid supplementation was associated with a reduction of the susceptibility of LDL particles to oxidation [80,81], another study failed to find an effect of ascorbic acid supplementation (at least 500 mg/day) [63]. Moreover, one study failed to find a significant effect of ascorbic acid supplementation on circulating LDL concentrations [82]. Even if ascorbic acid is water soluble and is not incorporated in LDL particles, it has been proposed that this vitamin may prevent LDL particle oxidation by scavenging free radicals and other reactive species in aqueous milieu [76].…”
Section: Ascorbic Acid Supplementsmentioning
confidence: 99%
“…We also extend the studies of Tousoulis et al [65] and Van Hoydonck et al [67] by examining two other major inflammatory molecules, (i) neutrophil elastase, a marker of neutrophil activation, and (ii) neopterin, a marker of monocyte activation. There was no statistically significant difference in neopterin or elastase concentrations between smokers and non-smokers at baseline.…”
Section: Discussionmentioning
confidence: 63%